Effects of ethyl acetate extract of peony (Paeonia suffruticosa) seed coat on the proliferation and apoptosis of oral squamous carcinoma cells through miR-424-3p/STAT3/Survivin pathway - Ren, Shipeng; Qing, Song (Cellular and Molecular Biology, 2020)
Oral squamous cell carcinoma is one of the most common high malignant tumors. This experiment aimed to investigate whether ethyl acetate extract of peony (Paeonia suffruticosa) seed coat could affect the proliferation and apoptosis of oral squamous carcinoma cells by regulating the miR-424-3p/STAT3/Survivin pathway. For this purpose, oral squamous cell carcinoma cell CAL27 was cultured in vitro, and cells were treated with ethyl acetate extract of peony seed coat at different concentrations. MTT was used to detect cell proliferation. Flow cytometry was used to detect apoptosis. qRT-PCR was used to detect the expression level of miR-424-3p. The miR-424-3p mimics and anti-miR-424-3p were transfected into CAL27 cells respectively, and the cell proliferation and apoptosis were detected by the above method. Western blot method was used to detect the expression of PCNA, Bcl-2, Bax, p-STAT3 and Survivin protein. Results showed that ethyl acetate extract of peony seed coat could reduce cell proliferation rate and the protein levels of PCNA, Bcl-2, p-STAT3, Survivin and the expression level of miR-424-3p (P<0.05), increase apoptosis rate and the protein level of Bax (P<0.05). After transfection with anti-miR-424-3p, the cell proliferation rate, the protein levels of PCNA and Bcl-2 were significantly reduced (P<0.05), the apoptosis rate and the protein level of Bax were significantly increased (P<0.05), while the effect of miR-424-3p mimics was the opposite. Transfection of miR-424-3p mimics could significantly reduce the regulatory effect of ethyl acetate extract of peony seed coat on CAL27 cell proliferation, apoptosis and STAT3/Survivin pathway. It concluded that ethyl acetate extract of peony seed coat could inhibit the activation of the STAT3/Survivin signaling pathway by down-regulating the expression of miR-424-3p, thereby inhibiting the proliferation of oral squamous carcinoma cells and inducing apoptosis.